Experimental and numerical research on the flow and heat transfer characteristics of TiO2-water nanofluids in a corrugated tube. (December 2017) - Qi, Cong; Wan, Yong-Liang; Li, Chun-Yang; Han, Dong-Tai; Rao, Zhong-Hao
Highlights: Resistance and heat transfer of nanofluids in a corrugated tube are studied. Effects of Peclet number and Reynolds number on heat transfer are investigated. Comprehensive performance of resistance and heat transfer enhancement is evaluated. Abstract: Flow resistance and enhanced heat transfer characteristics of TiO2 -water nanofluids in a stainless-steel corrugated tube and a circular tube are investigated by experimental and numerical methods respectively. The flow and heat transfer characteristics of TiO2 -water nanofluids and deionized water in test tubes are compared in this paper. In addition, effects of Reynolds number ( Re ) and nanoparticle mass fraction ( ω ) on flow and heat transfer performances are discussed respectively, and Nusselt number ( Nu ) and resistance coefficient ( f ) are studied respectively. Finally, comprehensive performance of flow resistance and heat transfer enhancement is evaluated. It can be obtained that adding nanoparticle into deionized water doesn't cause a large additional resistance loss in some degree, while the combination of corrugated tube and TiO2 -water nanofluids shows an excellent heat transfer enhancement, which can enhance the heat transfer by 53.95% at maximum extent. In addition, the corrugated tube has a strong sustainability in enhancing heat transfer. The enhanced heat transfer rising part (6000 ≤ Re ≤ 10, 000) has a large rising slope (about 7.90E−5), and the descending slope (about 7.16E−6) of enhanced heat transfer part (10, 000 ≤ Re ≤ 12, 000) is small.